Pendidikan Karakter Memperkuat Eksistensi Pendidikan Agama Hindu pada Era Industri 4.0 - Putu Ratni; I Nyoman Sueca (UHN IGB Sugriwa Denpasar, 2021)
This article is based on research that aims to align Hindu education with industrial development 4.0, which is an era of disruption in order to make it able to answer challenges also able to overcome the massive obstacles of Hindu education implementation without losing the essence of it. The research has been conducted by a qualitative approach; data were collected by the technique of observation, interview, documentation, and literature study; the data analysis utilized descriptive technique. The result of the research showed there are three important things that Hindu education needs to attempt, those are (1) switching the old mindset which is chained by the bureaucratic become the disruptive mindset that put cooperative ways forward, (2) applying self-driving in order to create reforms as the demand of 4.0 era, (3) has to be able to develop a digital basis new service system. Finally, it can be concluded that science and technology development in the global age delivers challenges and obstacles to Hindu education which also continues to develop and change. Therefore, Hindu education in this disruption revolution era 4.0 has been demanded to be sensitive to community social changing phenomenons, willing to do self-disruption through character education because if it persistence to stay on the old method and management also being sealed from the dynamic world, its existence will be slumped and underdeveloped.